Estatística Jubilar - Actas do XII congresso Anual da Sociedade Portuguesa de Estatística - Braumann, Carlos (2012)
Book of invited conferences and accepted refereed papers submitted to the Procedings of the XII Congresso Anual da Sociedade Portuguesa de Estatística (Évora, Portugal, 2005)